INNOVATIVE APPROACHES TO DEVELOPING AESTHETIC AND CREATIVE THINKING IN FINE ARTS EDUCATION - Sayfiyeva Ozoda Madamin qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article analyzes innovative approaches for developing students’ aesthetic and creative thinking in fine arts education. It examines effective strategies to enhance students’ visual thinking, artistic perception, and interest in art through interactive lessons, project-based learning, and digital tools. The study also emphasizes the significance of student-centered approaches and creative learning environments in fostering aesthetic thinking and artistic awareness.